Pengurangan Dampak Gangguan ( Interferensi ) Pada Jaringan Wi-fi Dengan Metode Pemisahan Geografis Dan Guard Band - Rangganis Rangganis; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Wi-Fi (Wireless Fidelity) is an application of WLAN (Wireless Local Area Network) using IEEE 802.11 standard. Wi-Ficommunication systems use radio networks with a frequency of 2,4 GHz, a weakness in wireless communication issusceptible to interference called co-channel and adjacent channel. In this research solution given by two methodscalled geographical separation and guard band. Geographical separation is a method that is done by giving thedistance between two interconnecting devices. Separation based on the scope of the coverage area of the device that isby gradually shifting until no interference occurs again. Guard band method is a method by giving the space band onboth interconnected channels of 3 MHz. In this study the parameter in the analysis is the SNR (Signal to Noise Ratio)value, the lowest SNR value occurs in the geographical separation method at a distance of 10 meters on signal channel1 with signal channel noise 1 is 12 dB when interference co-channel. The highest SNR value occurs in testinggeographic separation method in channel 7 with signal channel noise 4 at a distance of 40 meters when adjacentchannel interference occurs is 56 dB. Research result shows the most effective method to reduce the impact ofinterference is the geographical separation method.Keywords: Geographical separation, guard band, interference, Wi-Fi.